PENGGUNAAN MEDIA PEMBELAJARAN FILM DOKUMENTER PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM (SKI) KELAS VIII C DI MTs KEBUNREJO GENTENG BANYUWANGI - Ahmad Izza Muttaqin; Mohammad Afton Fahmi Prayogie; Riza Faishol (Jurnal Tarbiyatuna : Kajian Pendidikan Islam, 2021)
Based on observations made by researchers at MTs Kebunrejo Genteng, it turns out that there are still many weaknesses and obstacles faced, especially in learning (SKI). This was strengthened based on the results of interviews with some eighth grade students, their understanding in the learning process was felt to be lacking because most of them assumed that subjects (SKI) were subjects that tended to be less interesting and boring, because students had to memorize years or names. figure. Because it is considered a boring subject which in the end has an impact on the students' lack of understanding in receiving the subject matter, this can be seen in the odd semester scores on the material of the Islamic dynasty. This can be proven from 34 students of which 14 students scored below the minimum completeness criteria (KKM), namely 7. Based on the above problems, the researcher intends to describe the problem by using a learning medium that can help students understand the learning material. The learning media used were documentary films. The results of research on the use of documentary film learning media in class VIII C students at MTs Kebunrejo Genteng are that students are easier to understand and memorize Islamic dinasty subject matter (Ayyubiyah), student interest in learning is better than before, and students can achieve the above score (KKM) that is the value 7.